Fallstudie av mellanrummen i stadsdelen Ålidhems offentliga utemiljöer - Rubinsson, Carola (SLU/Dept. of Urban and Rural Development, 2007)
This diploma-work assess the public outdoor space. It has its starting point in, Ålidhem, a town district of Umeå. I have been studying public spaces in the outdoor environment. In this essay this refers to the spaces between the houses. What they are, what they contain, how they function and how they can improved. The focus has been on describing what's important in the spaces between the houses and how one can think in order to design a good outdoor environment. I have chosen to define a "good outdoor environment" as an environment that is social, safe, rich in experiences, aesthetic and has an identity.